2019
DOI: 10.1029/2018jc014648
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Intergeneric Variation in Physiological Indicators of Corals in the South China Sea: Insights Into Their Current State and Their Adaptability to Environmental Stress

Abstract: It is well known that coral thermal bleaching is mainly caused by abnormally high temperatures, but the spatial/intergeneric variation in coral‐algal symbiosis and its linkage to coral bleaching susceptibility is not well understood. In this study, 654 coral samples were collected from six coral reef regions (CRRs) in the South China Sea (SCS), between the Nansha Islands (~10°N) and Daya Bay (22°50′N). They were analyzed to explore how geographical/environmental variation affects coral bleaching susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 72 publications
(153 reference statements)
2
40
0
Order By: Relevance
“…That is to say, higher ZD may be lead to higher reactive oxygen species production under high‐temperature condition and then exacerbate climate‐change‐induced coral bleaching (Cunning & Baker, 2013). Nevertheless, the intergeneric variation pattern of ZD in our study is consistent with the results of previous studies in field conditions in the SCS that ZD of relatively stress‐tolerant massive corals are significantly higher than that of relatively vulnerable plating and branching corals (Li et al, a, ; Qin et al, ; Xu et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…That is to say, higher ZD may be lead to higher reactive oxygen species production under high‐temperature condition and then exacerbate climate‐change‐induced coral bleaching (Cunning & Baker, 2013). Nevertheless, the intergeneric variation pattern of ZD in our study is consistent with the results of previous studies in field conditions in the SCS that ZD of relatively stress‐tolerant massive corals are significantly higher than that of relatively vulnerable plating and branching corals (Li et al, a, ; Qin et al, ; Xu et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In the Nansha Islands (i.e., the Spratly Islands, southern South China Sea (SCS)), coral bleaching events, such as GCBEs, are one of the main threats to coral health, and lead to coral reef degradation and macroalgae occupation (e.g., Li et al, 2011;Yu et al, 2006). In situ observation during an investigation in June 2015 found that corals were in a healthy state such that almost no bleaching corals were found (e.g., Qin et al, 2019). In June 2016, the global El Niño event resulted in high SST anomalies such that corals suffered from high thermal stress.…”
Section: 1029/2019jc015579mentioning
confidence: 99%
“…In the South China Sea, coral reefs at low latitudes are also often subjected to unusually high temperatures. Statistics show that the Nansha Islands (where XyR and SjR are located) had annual maximum temperatures between 30 and 31 • C from 1985 to 2015 (Qin et al, 2019). The coral reefs located in high-latitude regions (e.g., Lht and DyB) are affected by human activities all year, resulting in serious eutrophication of the surrounding seawater.…”
Section: Discussionmentioning
confidence: 99%
“…The coral reefs located in high-latitude regions (e.g., Lht and DyB) are affected by human activities all year, resulting in serious eutrophication of the surrounding seawater. The live coral cover rapidly decreased from greater than 60% to less than 20% from 1984 to 2015 (Zhao et al, 2012;Qin et al, 2019). Diazotrophs are essential components of coral holobionts, which are involved in the nitrogen cycle (Piniak et al, 2003;Olson et al, 2009) and are important for energy supply (Hamilton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%